A material removal and surface roughness evolution model for loose abrasive polishing of free form surfaces. (24th November 2014) - Wan, Stephen; Liu, Yuchan; Woon, Keng Soon; Tnay, Guan Leong
We report on the development of a simple process model, motivated by a need to predict the evolution of surface roughness and geometrical change over external, three dimensional free form surfaces undergoing a loose abrasive polishing process. To this end, the process model was derived from tribological wear laws and cast in terms of the point sliding velocity and apparent pressure and then benchmarked against data drawn from experiments in three disparate loose abrasive finishing techniques, namely, vibratory finishing, abrasive flow machining and magnetorheological finishing. We conclude with a brief discussion on the potential and limitations of the model in analysing loose abrasive finishing processes.